Experimental Evidence of Chemical Components in the Bonding of Helium and Neon with Neutral Molecules. Issue 16 (6th March 2015) - Cappelletti, David; Bartocci, Alessio; Grandinetti, Felice; Falcinelli, Stefano; Belpassi, Leonardo; Tarantelli, Francesco; Pirani, Fernando
Abstract The complexes of helium and neon with gaseous neutral molecules are generally perceived to be van der Waals adducts held together by physical (non‐covalent) forces, owing to the combination of size (exchange) repulsion with dispersion/induction attraction. Molecular beam experiments confirm that this is the case for He–CF4, Ne–CF4 adducts, but revealed that the interaction of He and Ne with CCl4 features an appreciable contribution of chemical components that arise from the anisotropy of the electron density of CCl4 that enhances a charge transfer from Ng (Ng=He, Ne). These findings furnish a novel assay of the bonding capabilities of helium and neon, and invite to revisit the neutral complexes of these elements as systems of chemical relevance. The CCl4–Ng are also peculiar examples of halogen bonds, a group of interactions of major current concern. Finally, this investigation is a prelude to the development of semi‐empirical models for force fields aimed to the unified description of static and dynamical properties of systems of comparable or higher complexity.